2012
DOI: 10.1007/s10549-012-2367-z
|View full text |Cite
|
Sign up to set email alerts
|

Given breast cancer, is fat better than thin? Impact of the estrogen receptor beta gene polymorphisms

Abstract: Given breast cancer, is fat better than thin? Impact of the estrogen receptor beta gene polymorphisms.Borgquist, Signe; Hjertberg, Maria; Henningson, Maria; Ingvar, Christian; Rose, Carsten; Jernström, Helena Link to publication Citation for published version (APA): Borgquist, S., Hjertberg, M., Henningson, M., Ingvar, C., Rose, C., & Jernström, H. (2013). Given breast cancer, is fat better than thin? Impact of the estrogen receptor beta gene polymorphisms. Breast Cancer Research and Treatment, 137(3), 849-86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Mousa et al [15] demonstrated that a lower BMI is associated with a shorter disease-free survival (DFS) in patients with early stage breast cancer. Similarly, Borgquist et al [16] showed that overweight may be protective in breast cancer patients with certain ERbeta genotypes.…”
mentioning
confidence: 93%
“…Mousa et al [15] demonstrated that a lower BMI is associated with a shorter disease-free survival (DFS) in patients with early stage breast cancer. Similarly, Borgquist et al [16] showed that overweight may be protective in breast cancer patients with certain ERbeta genotypes.…”
mentioning
confidence: 93%
“…Valid tumor ERb1 scores were obtained from 911 patients (88.8% 10 expression was not significantly associated with the four germline ERb htSNPs or the two haplotypes "any TCAC" or the number of CCGC, either overall or in patients with BMI !25 kg/m 2 , where two htSNPs and the two haplotypes were differently associated with DFS depending on BMI in our previous report (3).…”
Section: Patient and Tumor Characteristics By Erb1 Statusmentioning
confidence: 55%
“…Genotyping of the ESR2 htSNPs (rs4986938, rs1256031, rs1256049, and rs3020450) was performed, and haplotypes were constructed as described previously (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 levels and body constitution are closely linked. Body constitution-related parameters, such as obesity, a high WHR, and a large breast volume, are associated with breast cancer prognosis [ 27 , 45 , 46 ]. This association is believed to be mediated by chronic inflammation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%